(untitled) (Homoeopathy for All, 2024)
Fungal infections, or mycosis, are diseases caused by a fungus (yeast or mold). There are millions of species of fungi. They live in the dirt, on plants, on household surfaces, and on skin. Sometimes, they can lead to skin problems such as rashes or bumps. Homoeopathy treats the individual in disease and not the disease alone and holistically helps the patient in need. Thus by striking at the root of the problem patient can be relieved from further remission of suffering.